Effect of fermentation on the nutritional composition antioxidant properties and anti-nutritional content of pineapple ananas comosus fruit processing waste - Catane, Karen Lihay-Lihay; Anuevo, Gwen Manero; Choresca, Jr., Casiano Hermopia; Özdemir, Keriman Yürüten; Pedroso, Fiona Lasanas (Journal of Food Technology Research, 2025)
The Philippines is among the top global producers of pineapple (Ananas comosus), selling it as fresh fruit and canned products in local and international markets. Escalating demand for these products has resulted in the accumulation of processing waste in pineapple plantations and nearby landfills, leading to environmental hazards. This pressing scenario calls for the value addition of pineapple fruit processing waste (PFPW) as a sustainable waste management strategy. The study assessed the viability of using molasses to ferment PFPW. Molasses concentrations of 0%, 10%, 20%, and 30% were tested to enhance the proximate composition, phytochemical content, antioxidant activity (using DPPH assay), and to reduce the anti-nutritional content of PFPW. Significant results indicated a positive effect of fermentation on the proximate composition of PFPW, resulting in increased carbohydrates (3–15%), crude protein (7–45%), crude fat (6–52%), ash (93–238%), and reduced fiber (9–50%) compared to unfermented PFPW. Additionally, there was a very significant increase in phytochemical content: total phenolic content (TPC) by 105–395% and total flavonoid content (TFC) by 306–744%, leading to increased free radical scavenging activity of the fermented samples by 67–192%. Furthermore, reductions in anti-nutritional content, such as tannin by 45–56% and phytate by 10–40%, were also observed. These findings suggest that fermented PFPW can serve as a potential low-cost aquaculture feed additive, contributing to sustainable waste management and resource utilization.